2007
DOI: 10.1103/physrevlett.98.098302
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Vibrational Energy Transfer between Surface and Bulk Water at the Air-Water Interface

Abstract: We report a femtosecond time-resolved study of water at the neat water-air interface. The O-H stretch vibrational lifetime of hydrogen-bonded interfacial water is measured using surface-specific 4th-order nonlinear optical spectroscopy with femtosecond infrared pulses. The vibrational lifetime in the frequency range of 3200 to 3500 cm(-1) is found to closely resemble that of bulk water, indicating ultrafast exchange of vibrational energy between surface water molecules and those in the bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 28 publications
6
113
1
3
Order By: Relevance
“…6 Nonetheless, in spite of a considerable effort in studying the dynamics and intermolecular coupling of water molecules bound to the different interfaces, the overall picture still remains controversial. For instance, sum-frequency generation (SFG) studies on water-silica 32 and water-air 33 interfaces have shown, quite surprisingly, that despite noticeable differences in spectral responses, the OH stretch vibrational dynamics of the surface water molecules are hardly distinguishable from those in the bulk. This suggests that water molecules at the surface are coupled either among themselves or to the water in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%
“…6 Nonetheless, in spite of a considerable effort in studying the dynamics and intermolecular coupling of water molecules bound to the different interfaces, the overall picture still remains controversial. For instance, sum-frequency generation (SFG) studies on water-silica 32 and water-air 33 interfaces have shown, quite surprisingly, that despite noticeable differences in spectral responses, the OH stretch vibrational dynamics of the surface water molecules are hardly distinguishable from those in the bulk. This suggests that water molecules at the surface are coupled either among themselves or to the water in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%
“…One direction that has been conventionally pursued is the removal of the complications related to the intra-and intermolecular couplings between the OH oscillators by substitution H 2 O with its deuterated isotope HDO. [11][12][13]16 Another possibility, which also mimics biological situations, 17 is to alter the complexity of the hydrogen bond network by studying water at interfaces, 18,19 in reverse micelles, [20][21][22][23][24][25][26][27] or in mixtures with various solvents. 11,28,29 The last setting is particularly advantageous because it allows investigating spatially separated water molecules and, thus, provides a unique opportunity to study purely intramolecular properties, which are not screened by interactions with other water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the ultrafast dynamics of the hydrogen bond network at water interfaces have been started. [11][12][13][14][15] In particular, Bonn and co-workers carried out two-dimensional (2D) VSFG spectroscopy at the surface of heavy water (D 2 O). 16 So far, however, the time-resolved and 2D VSFG experiments at the air/water interfaces have been performed with the conventional intensity-detection scheme that can only provide |χ (2) | 2 (χ (2) : second-order nonlinear optical susceptibility).…”
mentioning
confidence: 99%